The Use of Poster Media to Improve Students' Arabic Speaking Skills at SMP Al-Hikmah 2 Cirebon - Gunawan, Wawan; Dindawati, Triska; Alkayisy, Muhammad Ilyas (AS-SABIQUN, 2023)
Learning Arabic speaking skills that takes place at SMP Al-Hikmah 2 Cirebon is not running optimally, because it is not given enough attention. By seeing students who like visual media, the use of learning media in the form of posters can be a solution to learning problems. The purpose of this study was to determine students' speaking skills before using poster media, to determine students' speaking skills after using poster media and to determine the improvement of students' speaking skills using poster media. This research uses a quantitative approach in the form of experimental research with a one group pretest-posttest research design by conducting a pretest and posttest and then comparing scores before using poster media and after using it. Samples were taken by purposive sampling technique. Data collection techniques with observation, documentation, and tests. And data analysis using t-test. The results showed that: 1) students' speaking skills before using poster media could be seen from the pretest score which had an average of 38.86 which was considered very low. 2) students' speaking skills after using poster media can be seen from the posttest score which has an average of 67.05 which is higher than the pretest score. 3) the results of the t test show that the value of t count > t table (18.456 > 2.074) and sig. (2-tailed) < 0.05 (0.000 < 0.05). So, it can be concluded that the use of poster media is effective in improving students' Arabic speaking skills at SMP Al-Hikmah 2 Cirebon.